ORGANIZATIONAL MECHANISM OF ADMINISTRATIVE SERVICES IN THE COMMUNITY IN CONDITIONS OF DECENTRALIZATION - Mamonova V.V. (Pressing Problems of Public Administration, 2015)
Is substantiated a complex organizational mechanism of administrative services in thecommunity, defined its part – the structurally-organizational (aggregate of subjects appeal andsubjects administrative services, and their powers and responsibilities) and functionallymethodological(includes the following components – kinds of activity, list and registry services,monitoring; methodology; technology and toolkit).